Reglas de derivación

Suma Producto

www.vaxasoftware.com

y=u + v
Resta

y ' = u ' + v'
y ' = u ' − v'

y=uv
Cociente

y ' = u ' v + v' u

y=u − v

y=

u v

y' =

u ' v − v' u v2

y=k
y=x

y' = 0
y' = 1 y' = k y=u y=ku

y' = u'
y' = k u'

y=k x

y=

1 x

y' =

y = x2

−1 x2 y' = 2 x

y=

1 u

y' =

y = u2

− u' u2 y' = 2 u u'

y = xn
y = ex y = ax
y = ln x y = log a x

y ' = n x n −1
y' = e x

y = un
y = eu y = au
y = ln u y = log a u

y ' = n u n −1 u ' y ' = u ' eu y ' = u ' a u ln a
y' = y' = u' u u' u ln a

y ' = a x ln a
y' = 1 x

y' =

1 x ln a

y=

x

y' =

1 2 x

y= u
y = sen u y = cos u

y' =

u' 2 u

y = sen x y = cos x

y ' = cos x

y ' = u ' cos u y ' = −u ' sen u ⎧ y ' = (1 + tan 2 u ) u ' ⎪ u' ⎨ = = u ' sec 2 u 2 ⎪ cos u ⎩

y ' = − sen x
⎧ y ' = 1 + tan 2 x ⎪ 1 ⎨ = = sec 2 x 2 ⎪ cos x ⎩ y' = y' = −1 = − cosec 2 x 2 sen x 1 1− x2

y = tan x y = cotan x
y = arcsen x y = arccos x

y = tan u y = cotan u
y = arcsen u y = arccos u

y' = y' =
y' =

− u' = − u ' cosec 2u 2 sen u u' 1 − u2
−u' 1 − u2

y' =

−1 1 − x2

y = arctan x
Derivación logarítmica

y' =

1 1+ x2

y = arctan u
2) ln y = ln( u v )

y' =

u' 1 + u2
3) ln y = v ln u

1) y = u v 4)

y' u' = v' ln u + v y u

u' ⎞ ⎛ 5) y ' = y ⎜ v' ln u + v ⎟ u ⎠ ⎝

u' ⎞ ⎛ 6) y ' = u v ⎜ v' ln u + v ⎟ u ⎠ ⎝

Siendo: y, u, v funciones de x;

a, k, n constantes.

Sign up to vote on this title
UsefulNot useful